DEVELOPMENT TEACHING MATERIAL OF ELEMENT PERIODIC PROPERTIES AT BASIC CHEMISTRY I EDUCATION CHEMISTRY PROGRAM DEPARTMENT OF UPR - Mulawi; Wahyu Nugroho (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
Students' learning outcomes in the chemistry education course FKIP University of Palangka Raya, shows students tend to have difficulty in understanding the concept, especially the properties of the period keperiodikan. One of the causes of low learning outcomes is the availability of books used as a learning resource for students. Based on the observation result, chemical learning resources in basic chemistry lecture I still have deficiency, that is not based on REACT (relating, experimenting, applying, cooperating, transferring). Therefore, to increase students' interest and motivation, it is better to conceptualize the nature of the periodicity of the elements in the form of development of teaching materials. The research will be conducted on students who are taking Basic Chemistry course I in Chemistry Education Study Program PMIPA FKIP Universitas Palangka Raya, Central Kalimantan. The design of teaching materials development is designed with attention to several aspects such as, aspects of definition, design, development, and testing on students.